FEATURES OF MAGNETOVIBRATING TECHNOLOGIES OF SLIME SEPARATION IN GRINDING MANUFACTURE - Yury Mikhaylovich Vernigorov (Advanced Engineering Research, 2012)
The metal recovery goes from 0,4 up to 0,95 under the machine waste reclamation by the powder metallurgical techniques. Energy costs on the article production decrease. Under separating the slime produced in steel parts grinding, the promising approach is the liquefaction of dispersed ferromagnetic materials in the magnet field. In the nonuniform electromagnetic field, slime conglomerates holding the abrasive are effectively failing with the result that a qualitative splitting of magnetic and nonmagnetic slime fractions is possible. The mechanism and basic blocks of the magnetovibrating technology of the swarf separation for the bearing manufacturing are described. The determination technique of the magnetic fields optimum performance, when the effective splitting of the magnetic and nonmagnetic slime fractions is conducted, is resulted. The quoted simulation model allows define a gradient interval of the variable magnetic field induction at which the grinding slime conglomerates fail. The abrasive separated from slime was used through the investment casting. The slime metal component was used in the process of electrode coating for arc welding.